Early Intra-Abdominal Bacterial Infections after Orthotopic Liver Transplantation: A Narrative Review for Clinicians - Riccardo Taddei; Niccolò Riccardi; Giusy Tiseo; Valentina Galfo; Giandomenico Biancofiore (MDPI AG, 2023)
Despite recent advances in the transplant field, infectious complications after orthotopic liver transplantation (OLT) are major causes of morbidity and mortality. Bacterial intra-abdominal infections (IAIs) are predominant during the first month post-transplantation and affect patient and graft survival. Recently, the emergence of multidrug resistant bacteria has generated great concern in OLT patients. We performed this narrative review of the literature in order to propose a "ready-to-use" flowchart for reasoned empirical antibiotic therapy in the case of suspected post-OLT IAIs. The review was ultimately organized into four sections: "Epidemiology and predisposing factors for IAI"; "Surgical-site infections and perioperative prophylaxis"; "MDRO colonization and infections"; and "Reasoned-empirical antibiotic therapy in early intra-abdominal infections post OLT and source control". Multidisciplinary teamwork is warranted to individualize strategies for the prevention and treatment of IAIs in OLT recipients, taking into account each patient's risk factors, the surgical characteristics, and the local bacterial epidemiology.